Exploring the Role of Arsenic trisulfide in Ayurvedic Pharmacology: Insights from Bhaishajya Ratnavali - Premadevi Ramdasji Kalmegh; Bharat Rathi (International Journal of Medical Toxicology and Legal Medicine, 2025)
Arsenic trisulfide (Hartala), a traditionally categorized DhatujaVisha in Ayurveda, has long been incorporated in therapeutic formulations, especially within the classical compendium BhaishajyaRatnavali. This review investigates the pharmacological applications, formulation prevalence, dosage patterns, and safety protocols associated with Hartala-based formulations. The paper underscores the significance of Shodhana (purification), methodical dosing, and Rasashastra principles ensuring therapeutic benefits with minimal toxicity. Contemporary pharmacological evaluations reveal promising antibacterial properties of Hartalabhasma, warranting further clinical exploration. The study attempts to synthesize traditional wisdom with modern research to facilitate future integration into evidence-based healthcare.